Combined branch retinal vein and artery occlusion in toxoplasmosis - Aggio,Fabio Bom (2016)
ABSTRACT A 22-year-old man complained of low visual acuity and pain in his left eye for five days. His ophthalmological examination revealed 2+ anterior chamber reaction and a white, poorly defined retinal lesion at the proximal portion of the inferotemporal vascular arcade. There were retinal hemorrhages in the inferotemporal region extending to the retinal periphery. In addition, venous dilation, increased tortuosity, and ischemic retinal whitening along the inferotemporal vascular arcade were also observed. A proper systemic work-up was performed, and the patient was diagnosed with ocular toxoplasmosis. He was treated with an anti-toxoplasma medication, and his condition slowly improved. Inferior macular inner and middle retinal atrophy could be observed on optical coherence tomography as a sequela of ischemic injury. To our knowledge, this is the first report of combined retinal branch vein and artery occlusion in toxoplasmosis resulting in a striking and unusual macular appearance.